Venous Thromboembolism in Hospitalized Patient with Heart Failure, Does Heart Failure Increase the Risk of Dvt? - Yuri Savitri; Aragibinafika Aragibinafika; Lisna Agiara; Nurhafizah Muzainy; Nanda Chairina; Dwi Novlita Rozi (International Journal Labs, 2022)
Background: Deep vein thrombosis (DVT) is frequently observed in patients with chronic heart failure (CHF), increasing the risk of pulmonary embolism (PE). Clinical evaluation of CHF patients with suspected acute PE is challenging since these diseases share several symptoms and signs such as dyspnea. Objective: The aim of this study was to analyze whether heart failure increases the risk of DVT. Method: This study uses a qualitative approach with a case study model that analyzes and identifies venous thromboembolism in hospital patients with heart failure, does heart failure increase the risk of DVT? Result: DVT (Deep Vein Thrombosis) is the formation of a thrombus or blood clot that often attacks the deep veins of the lower extremities (such as the calf, femoral and popliteal veins) or deep veins in the pelvic area, more frequent in proximal than distal DVT. This condition is potentially dangerous, leading to morbidity and mortality that can essentially lead to disease. This happens all over the world. In general these diagnoses are combined in VTE (Venous Thromboembolism). In patients with DVT without PE, short-term mortality rates of 2–5% were reported. Recurrence risk is high, especially within first 6 months. Conclusion: From the results obtained we can know that Symptomatic patients with proximal DVT may present with lower extremity pain, calf tenderness, and lower extremity swelling (Kesieme et al., 2011) Same with this case, Patient was admitted to the hospital with complaints swelling of the whole body, especially the legs accompanied by pain, redness, feel warmed a few hours before the patient going to hospital.